Demographic Factors and BMI on Declined Lung Function and Vitamin D Levels in Active Smokers - Laksono, Pandu; Lorensia, Amelia; Wijono, Heru (Jurnal Kesehatan Masyarakat, 2025)
Cigarettes are one of the causes of health problems in the world. Smoking has been known to have a direct impact on reducing lung function. Smoking increases the risk of vitamin D deficiency. Vitamin D is a vital nutrient as a lung immunomodulator. Deficient levels will cause problems with lung health, especially in active smokers. This cross-sectional research using multivariate path analysis and the SEM-PLS method has three objectives. The direct influence of three independent variables, including obesity, smoking, and demographics. Regarding vitamin D status and lung function, analyzing the direct effect of vitamin D on lung function, and thirdly, analyzing the indirect one of the three independent variables on lung function through vitamin D levels. This research took time from October 2023 to January 2024 and involved 47 active smoker respondents whose vitamin D level status and lung function were measured. There was a significant direct effect of obesity level on vitamin D levels in the active smoker population (p<0.05;f-square=2.889). While demographic factors (p>0.05;f-square=0.030) and smoking frequency (p>0.05;f-square=0.003) did not have a direct significant effect. Demographic factors, obesity, and smoking frequency don’t have significant direct effect on lung function in active smokers (p>0.05).